Evaluation of Changes in Preoperative Cortical Excitability by Navigated Transcranial Magnetic Stimulation in Patients With Brain Tumor - Neville, Iuri Santana; Gomes dos Santos, Alexandra; Almeida, Cesar Cimonari; Hayashi, Cintya Yukie; Solla, Davi Jorge Fontoura; Galhardoni, Ricardo; de Andrade, Daniel Ciampi; Brunoni, Andre Russowsky; Teixeira, Manoel Jacobsen; Paiva, Wellingson Silva (Frontiers in Neurology, 2021)
Background: This prospective study aimed to evaluate the cortical excitability (CE) of patients with brain tumors surrounding or directly involving the corticospinal tract (CST) using navigated transcranial magnetic stimulation (nTMS). Methods: We recruited 40 patients with a single brain tumor surrounding or directly involving the CST as well as 82 age- and sex-matched healthy controls. The patients underwent standard nTMS and CE evaluations. Single and paired pulses were applied to the primary motor area (M1) of both affected and unaffected cerebral hemispheres 1 week before surgery. The CE parameters included resting motor threshold (RMT), motor evoked potential (MEP) ratio for 140 and 120% stimulus (MEP 140/120 ratio), short-interval intracortical inhibition (SICI), and intracortical facilitation (ICF). Motor outcome was evaluated on hospital discharge and on 30-day and 90-day postoperative follow-up. Results: In the affected hemispheres of patients, SICI and ICF were significantly higher than in the unaffected hemispheres (p=0.002 and p=0.009, respectively). The 140/120 MEP ratio of patients' unaffected hemispheres was lower than that in controls (p=0.001). Patients with glioblastomas (GBM) had a higher interhemispheric RMT ratio than patients with grade II and III gliomas (p = 0.018). A weak correlation was observed among the RMT ratio and the preoperative motor score (R2 = 0.118, p = 0.017) and the 90-day follow-up (R2 = 0.227, p = 0.016). Conclusion: Using preoperative nTMS, we found that brain hemispheres affected by tumors had abnormal CE and that patients with GBM had a distinct pattern of CE. These findings suggest that tumor biological behavior might play a role in CE changes.